The story of Emily - Lori Jennings; Barb O'Neil; Kim Bossy; Denise Dodman; Jill Campbell (The Beryl Institute, 2016)
This case study describes Bluewater Health's quest to weave the philosophy and practice of patient and family-centered care from the boardroom to the bedside by introducing Emily. Emily's image is a composite of photographs of staff, physicians, volunteers, patients and families exemplifying that each has a role in Emily's care. Emily represents every patient and family of the past, present, and future. Emily's journey started with the launch of Bluewater Health's 2013-2015 strategic plan and moved throughout the organization as patient councils were established and the organization embedded three foundational patient and family-centered RNAO Best Practice Guidelines into daily practice with the support of over 100 best practice champions. The successful implementation of RNAO's best practice guidelines earned Bluewater Health designation as a Best Practice Spotlight Organization. The organization took a risk in introducing the notion of Emily knowing that Emily could become a cliché. No one was prepared for what has come to be known as "the Emily effect." Emily's effect is now being realized in increased patient satisfaction and improved employee engagement scores helping to deliver on our Mission, We create exemplary healthcare experiences for patients and families every time. Bluewater Health is a fully accredited, 326-bed community hospital that cares for the residents of Sarnia-Lambton, Ontario.